Irritable bowel syndrome among Japanese adolescents: A nationally representative survey. Issue 9 (September 2015) - Yamamoto, Ryuichiro; Kaneita, Yoshitaka; Osaki, Yoneatsu; Kanda, Hideyuki; Suzuki, Kenji; Higuchi, Susumu; Ikeda, Maki; Kondo, Shuji; Munezawa, Takeshi; Ohida, Takashi
Abstract Background and Aim No nationally representative survey of irritable bowel syndrome (IBS) among adolescents has ever been performed in Japan. In the present study, we aimed to clarify the prevalence of IBS among Japanese adolescents and the factors associated with it. Methods The items related to the diagnostic criteria for IBS based on the Rome III Diagnostic Criteria for Functional Gastrointestinal Disorders were included in a cross‐sectional nationwide survey of "alcohol consumption and smoking habits among junior and senior high school students." The participating schools were sampled from among all junior and senior high schools in Japan using the cluster‐sampling method, and self‐administered questionnaires were sent to the selected schools by mail. Among 99 416 questionnaires that were collected, data from 98 411 valid responses were analyzed. Results The results showed that the prevalence of IBS was 18.6%. Although no sex difference was observed in the overall prevalence of IBS, the prevalence of diarrhea‐predominant IBS was higher among boys than among girls, and the prevalence of constipation‐predominant IBS was higher among girls than among boys. The prevalence of IBS increased with progression of the school grade, and there were the significant relationships between IBS and sleep‐phase delay and insomnia symptoms. IBS was also significantly associated with poor mental health status. Conclusion These results indicate that IBS is common among junior and senior high school students, and associated with lifestyle and mental health.